Novel composite material SiO2-Cd2SiO4@CdS: Synthesis, properties, application - Gotovtseva, Ekaterina Yu (Key engineering materials)
SiO2-Cd2SiO4@CdS multicomponent composite materials were synthesized in several stages. The structure and morphology of powders obtained were studied. According to scanning electron microscopy data the size of individual particles was about 400 nm. Specific surface area for all the samples did not exceed 1 cm2/g. It was found, that in contradistinction to CdS, composites obtained had high photo-corrosion resistance both to visible and ultraviolet light. On the example of photodegradation of the dye Nile blue in water, it was shown that SiO2-Cd2SiO4@CdS composites had high photocatalytic activity in visible range.